2018
DOI: 10.1016/j.jcou.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

CO2 reforming of methane over Ni-Ru supported catalysts: On the nature of active sites by operando DRIFTS study

Abstract: The present paper addresses the nature of the active sites of a bimetallic Ni-Ru supported catalyst on the dry reforming of methane (DRM). The structural characterization by XRD and Raman spectroscopy, along with the reducibility study (TPR-H2) of the samples, evidenced the existence of a strong Ni-Ru interaction in the bimetallic system. We have assumed that Ru atoms block the most reactive Ni sites (step-edge sites) leaving less reactive centers for methane activation (terraces). In this way, operando DRIFTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(8 citation statements)
references
References 57 publications
0
7
1
Order By: Relevance
“…Several pretreatment conditions were studied, which included calcined (C), calcination-reduction (CR), and direct reduction (DR). The Ru x Ni y Mg 1-x-y O catalysts prepared via DR pretreatment method demonstrated In contrast to previously reported results, Á lvarez et al [14] showed that monometallic Ni/MgAl (CH 4 conversion = 55 %, CO 2 conversion = 70 %) presented the highest catalytic activity, followed by Ni-Ru/MgAl (CH 4 conversion = 30 %, CO 2 conversion = 40 %) and Ru/MgAl (CH 4 conversion = 5 %, CO 2 conversion = 10 %). The lower catalytic activity in the bimetallic Ni-Ru catalyst could be caused by the altering in the electronic structure of Ni metal by Ru metal which covered the step-edge sites of Ni particles, which consequently forbade the more dominant Ni step-edge sites and shifted to less sensitive Ni terrace sites for methane activation.…”
Section: Introductioncontrasting
confidence: 73%
“…Several pretreatment conditions were studied, which included calcined (C), calcination-reduction (CR), and direct reduction (DR). The Ru x Ni y Mg 1-x-y O catalysts prepared via DR pretreatment method demonstrated In contrast to previously reported results, Á lvarez et al [14] showed that monometallic Ni/MgAl (CH 4 conversion = 55 %, CO 2 conversion = 70 %) presented the highest catalytic activity, followed by Ni-Ru/MgAl (CH 4 conversion = 30 %, CO 2 conversion = 40 %) and Ru/MgAl (CH 4 conversion = 5 %, CO 2 conversion = 10 %). The lower catalytic activity in the bimetallic Ni-Ru catalyst could be caused by the altering in the electronic structure of Ni metal by Ru metal which covered the step-edge sites of Ni particles, which consequently forbade the more dominant Ni step-edge sites and shifted to less sensitive Ni terrace sites for methane activation.…”
Section: Introductioncontrasting
confidence: 73%
“…In Table 2, we have compiled the examples of preparation and application of Ru/Ni systems. wet impregnation, calcination dry reforming of methane [83] 15 wt.% Ni-0.5 wt.% Ru/MgO/Al 2 O 3 wet impregnation, calcination dry reforming of methane [84] 14 wt.% Ni-1 wt.% Ru/CeO 2 -Al 2 O 3 co-precipitation, wet impregnation, calcination hydrogen production via steam reforming of simulated bio-oil [10] 10 wt.% Ni-1 wt.% Ru/C incipient-wetness impregnation, calcination hydrogenolysis of lignin [11] Ni-Ru (various loading)/C chemical reduction, galvanic replacement, calcination catalic hydrogenation [85,86] 1 wt.% Ni-0.3 wt.% Ru/ZnSe: CGSe flux-assisted method, precipitation photocatalytic hydrogen evolution [87]…”
Section: Ru and Ni Combinations-preparation And Applicationsmentioning
confidence: 99%
“…They can also easily get deactivated at high temperatures by sintering and/or coke deposition and are particularly susceptible to sulfur poisoning, e.g., from H 2 S [80,91,97]. There are several solutions that can improve the performance and life span of this type of catalyst, for instance, using a support [83,91,[98][99][100], catalytic promoters [91,99,100], coupling with other non-noble elements into alloys or spinel structures [100,101], or composing bimetallics with noble metals [10,53,[74][75][76]84]. Ruthenium is one of the most used noble metals for this purpose.…”
Section: Ru/ni Catalysts For Low-temperature Co 2 (Co) Methanationmentioning
confidence: 99%
See 1 more Smart Citation
“…One method is to change the acidity and alkalinity of the catalyst carriers, such as MgO [11,12], Al 2 O 3 [12][13][14], CaO [15][16][17], and CeO 2 [18][19][20]. The second method is to dope a small amount of a noble metal such as Rh or a transition metal such as Co into a Ni-based catalyst to prepare a bimetallic catalyst [21][22][23]. The third is to choose different catalyst preparation methods, such as the preparation of Ni-based catalysts with core-shell structures [24][25][26][27][28][29][30], the preparation of Ni-based catalysts by plasma technology [10,31,32], and other methods [33,34].…”
Section: Introductionmentioning
confidence: 99%